A influência do interesse no uso das mãos em atividades diárias de crianças e jovens com paralisia cerebral - Rachel Helena Silva de Oliveira (2017)
The use of hands during daily activities can be a challenge for children and young people with spastic unilateral cerebral palsy (PCUE). While performing bimanual activities, these individuals may have difficulties in grasping, manipulating and releasing objects with the affected hand. Due to these difficulties, individuals with PCUE may avoid using the affected extremity while performing their routine activities. Even having to face these challenges, the interest of children and young people with PCUE in certain activities can influence the use of the affected extremity during daily activities. The general objective of the study was to investigate the influence of interest in activities of the daily routine in the use of hands of children and young people with PCUE, in their home environment. A cross-sectional observational study was carried out with 20 children and young people, aged between 8 and 14 years, with a diagnosis of PCUE. The participants in the study were those classified in levels I, II and III according to the Manual Ability Classification System (MACS) and scored 85 on the Kaufman Brief Intelligence Test (KBIT-2). Semi-structured interviews were conducted with participants who described their daily routine and chose bimanual activities considered to be within their interest and non-interest. The participants were filmed in the home environment while performing the chosen activities. The time of occurrence of parameters that characterized the way the affected hand was used and its effectiveness was documented, as well as the amount and type of support given by the caregiver and the demonstration of satisfaction when performing activities of interest and of non-interest. Datavyu 1.2.2 software was used to analyze the videos and identify the duration of each parameter in each activity. A total of 116 activities were analyzed, being 58 of interest and 58 non-interest. The Wilcoxon Signed-Rank test was used to compare the observation time of the parameters in the activities. There was evidence of an effect upon the interest of the child with reference to the type of physical support (p= 0.0304) and in the child's satisfaction during the activity (p= 0.0031). The direction of these effects indicated that children and young people received more physical support from their caregivers in non-interesting activities and showed greater satisfaction carrying out the activities of their interest. The effect of interest in the parameters of use, effectiveness and support was not observed. A model illustrating the effect of the interest in activities upon the bimanual performance of children and youngsters with PCUE was drawn from the results of the present study in combination with the literature evidence on the bimanual performance of children with PCUE. Some of the effects and directions illustrated in the model should be scientifically tested by future studies. Based on this model, it is suggested that promoting opportunities for practicing non-interesting activities for children and young people with PCUE can contribute to the expansion of their repertoire of skills, sense of efficacy and expectation of success, favoring the performance of bimanual activities.